ANALYSIS OF THE INFLUENCE OF OPERATIONAL COSTS ON INCREASING THE FINANCIAL PERFORMANCE OF AMERICAN PUBLIC HELATH CORPORATION - Bob Feinberg; Maurizio Zanardi (PT. Radja Intercontinental Publishing, 2022)
This study aims to find out how the effect of operational costs on improving the performance of American Public Helath Corporation. The research method used is quantitative data method. While the data used is secondary data. The method of data analysis in this study uses simple linear regression analysis to obtain a comprehensive picture of the effect of the variables on Operational Costs on Performance Improvement using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of testing the hypothesis using simple regression analysis and t-test show that: that the t-table value of the Operating Costs variable is 6.862 > the t-table value (df:α :